Hand washing knowledge and practices among public primary schools in the Kintampo Municipality of Ghana - Dajaan, Dubik S.; Addo, Henry O.; Ojo, Luke; Amegah, Kingsley E.; Loveland, Fiagbe; Bechala, Banewel D.; Benjamin, Begyele B. (International Journal Of Community Medicine And Public Health, 2018)
Background: Hand washing is very effective in preventing communicable diseases. Hand washing is particularly important for children, as they are more vulnerable to infections gained from unwashed hands and also due to their unhealthy behaviour. The study was conducted to determine the availability of hand washing facilities, hand washing knowledge and practices among public primary schools in Kintampo Municipality. Methods: A cross sectional survey was carried out among 300 children and 10 headmasters in 10 selected schools. Data were collected using questionnaires and observation checklist regarding socio-demographic characteristics, knowledge of hand washing, hand washing practices and availability of hand washing facilities in the selected schools. Results: All the children indicated that it was important to wash their hands with water and soap. About (37.67%) washed their hands in order to prevent diseases, 53.33% had never been educated on how to wash their hands. Only 23.33% of the children demonstrated correctly on how to wash hands, a little over 15% washed their hands under clean running water whiles 23.33% wipe their hands using handkerchiefs. Forty-three percent indicated after visiting toilet as necessary to wash hands whiles 42.33% cited lack of water as the barrier to hand washing. About 39.88% always washed their hands with soap after using the toilet; about 60% of the schools had hand washing points. Only 30% of the schools have clean running water. Conclusions: There is the need for effective hand washing education in the schools to help improve hand washing knowledge and practices. Hand washing facilities in the schools were found to be inadequate.